Ketersediaan hayati relatif furosemida dalam bentuk dispersi padat =Comparative Bio availability Furosemide in Solid Dispersion Forms - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Solid dispersion system of water-insoluble furosemide in polyvinylpirolidon (PVP) was prepared by a solvent method in various ratios of 1 : 5 and 1 : 7 of the drug and PVP, respectively in order to improve furosemide bioavailability. The bioavailability of furosemide - PVP solid dispersion was compared with pure furosemide (control) and Lasix® (reference). The study was done in a cross over design with a single-dose peroral that administered to the white male rabbits (n = 6). Furosemide blood levels were determined spectrofluorometrically by an extraction method. The area under the blood concentration-time curve AUC0 y peak blood concentration Cmax and time to reach peak blood concentration Tmax were used to compare their bioavailabilities. The solid dispersion systems produced a higher extent of bioavailability than pure furosemide (P < 0,05). On the contrary, no statistically significant difference the extent of bioavailability between solid dispersion and Lasix® (P > 0,05). Finally, furosemide - PVP solid dispersion (1: 7) was the best formulation with the highest extent of bioavailability and bioequivalence with the Lasix® formula's.